1999
DOI: 10.1039/a902621e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative IR and 1H-MAS NMR study of adsorption of CD3CN on zeolite H-β: evidence of the presence of two families of bridged Brnsted sites

Abstract: The IR and 1H-MAS NMR spectroscopy of zeolite H-b in interaction with is described. Two families of strong CD 3 CN Si(OH)Al sites have been clearly distinguished : a Ðrst BrÊnsted family, characterized by an NMR signal at 4.4 ppm and an IR peak at 3614 cm-1 (isolated bridged hydroxys) and a second family, characterized by a broad band in the 3-7 ppm NMR range and in the 3600-3200 cm-1 IR range, due to bridged hydroxys which are perturbed by H-bond interactions with the zeolitic framework. This last family of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 10 publications
3
34
0
Order By: Relevance
“…3), two main peaks are observed at 1.32 and 5.27 ppm due to protons of isolated and/or terminal SiO-H and H-bonded silanol groups at vacant T-atom sites, respectively, in line with earlier data on BEA [11,17,18], MFI [19,20], silicalite [21] and silica [22].…”
Section: H Mas Nmrsupporting
confidence: 83%
“…3), two main peaks are observed at 1.32 and 5.27 ppm due to protons of isolated and/or terminal SiO-H and H-bonded silanol groups at vacant T-atom sites, respectively, in line with earlier data on BEA [11,17,18], MFI [19,20], silicalite [21] and silica [22].…”
Section: H Mas Nmrsupporting
confidence: 83%
“…For MMT, the weak adsorption bands at 680 cm −1 , 841 cm −1 , 920 cm −1 and 1050 cm −1 are, Al-O stretching, O-H bending in Mg-Al-OH, O-H bending in Al-Al-OH and Si-O-Si stretching, respectively 35 . The band at 3623 cm −1 is ascribed to O-H stretching in Al-Si-OH 36 (Table S1). Surface aluminum ion is a strong Lewis acid and the edge hydroxyls are polarized as indicated by the pyridine adsorption study.
Figure 3Full IR spectra of RhB, MB, MMT, MMT/MB and MMT/RhB ( a ) and partial IR spectra (1200–1800 cm −1 ) showing residual bands after washing with water ( b ).
…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have demonstrated the heterogeneity of the Brønsted site strength [15,16,23]. The presence of very strong Brønsted sites has also been noticed in several works [11,15,16,24].…”
Section: Introductionmentioning
confidence: 86%
“…The strongest Brønsted sites would be located in the well crystallized areas, the weakest in the areas of lower crystallinity [15]. Pazè et al [23] have identified weak Brønsted sites as bridging hydroxyls perturbed by H-bond interaction with the zeolite framework. These sites give a broad IR band in the 3600-3200 cm -1 range.…”
Section: Introductionmentioning
confidence: 97%